Determination of optimal duration for Hypochlorite Bleaching for Sesbania grandiflora pulp - Liew, Jing Xian (2019)
Bleaching is a treatment of pulp with chemical to increase the brightness by altering or removing the residual lignin of the lignocellulosic material which causes the brown colour of the pulp through oxidation. Bleaching is able to increase the stability of paper colours and the paper product produce from bleached pulp has better capacity in receiving image from painting or writing. Sodium hypochlorite was used as the bleaching agent because of it strong oxidising bleaching in brightening the pulp. Sesbania grandiflora is a fast growing species with 3 to 4 years of harvest rotation and it potential to produce high cellulose content made it as a promised commercial pulp in Malaysia. In order to improve the over bleaching duration in pulp and paper field, the research was carried out with the aims to determine the optimal duration by bleaching the Sesbania grandiflora with sodium hypochlorite, meanwhile, evaluate the influence of bleaching duration on the Sesbania pulp properties and paper elements. Sesbania pulp was treated with 5.00wt% of sodium hypochlorite solution in the water bath under the temperatures of 50°C. Three bleaching durations were taken, which are 20 minutes, 40 minutes and 60 minutes. The procedures of handsheets testing were conducted according to TAPPI standard. The obtained results showed that 60 minutes was the optimal bleaching duration which showed the highest brightness percentage and the least lignin content. The reduction of lignin content also the kappa number will contribute to the brightness of the pulp. However, the overall strength properties of the Sesbania handsheets such as bursting test, tearing test and folding endurance test were decreased due to the fibre degradation when bleaching. The optical properties and strength properties of bleached handsheets showed significantly difference as compared to the unbleached handsheets and the difference become obvious as the bleaching duration increase.